A Ciência da Lógica e o problema da consistência de Hegel: considerações sobre Hegel e o princípio da não-contradição - Nascimento Júnior, Fábio Baltazar do (2012)
This work intends to discuss if Hegel s logic is classic or suspends the principle of non-contradiction. We tried to define this logical principle without presupposing any special ontology. We also analyzed some fundamental parts of the Science of Logic, which is a central work of Hegelian system. We believe that our arguments show that Hegel did not disobey the principle of non-contradiction, which can evaluate even ontology of contradiction.